“The Relationship Between Geometric Reasoning and the Learning of the Derivative in the Subject of Differential Calculus in University Students in the Period 2023-II” - Baltazar, Marisol Paola Delgado; Arenas, Ruben Dario Mendoza; Loli, Mónica Beatriz La Chira; Cruz, Josefina Arimatea García; Salazar, Jenny María Ruiz; Quispe, Ana Maria Holgado; Wong, Raquel Leonor Atoche; García, Jesselle Roxana Rodas; Morales, Ana María Yamunaqué (Migration Letters, 2024)
The research aimed to determine the relationship between geometric reasoning and the learning of the derivative in Differential Calculus. It employed a quantitative approach, specifically a basic type of research with a non-experimental design and a cross-sectional correlational method. The sample consisted of 80 students selected through a census approach. The survey technique was employed, and the instruments used were a questionnaire and a questionnaire test. The results indicated that 73.7% of the participants were at a medium level of the geometric algorithm, while 47.5% were at a regular level of learning the derivative. A statistical analysis using Spearman’s rho revealed a correlation coefficient of 0.769, with a significance level of 0.000 (p<0.05). This suggests a direct, high, and significant relationship between the geometric algorithm and the learning of the derivative in the context of Differential Calculus in university students in the period 2023-II. In conclusion, the research establishes a strong connection between the proficiency in geometric reasoning, as measured by the geometric algorithm, and the level of learning of the derivative in the specified calculus course. These findings contribute to understanding the interplay between geometric reasoning and mathematical learning in the context of Differential Calculus.